Challenges to diagnosing and managing preeclampsia in a low-resource setting: A qualitative study of obstetric provider perspectives from Ghana. - Namratha Atluri; Titus K Beyuo; Samuel A Oppong; Cheryl A Moyer; Emma R Lawrence (PLOS Global Public Health, 2023)
Preeclampsia is a leading cause of global maternal morbidity and mortality. The greatest burden of disease is in low- and middle-income countries where healthcare providers face significant, understudied, challenges to diagnosing and managing preeclampsia. This qualitative study used semi-structured interviews to explore the challenges of diagnosing and managing preeclampsia from the perspectives of obstetric doctors. Participants were doctors who provide obstetric care at the Korle Bu Teaching Hospital, an urban tertiary hospital in Ghana. Purposive sampling identified doctors with meaningful experience in managing patients with preeclampsia. Thematic saturation of data was used to determine sample size. Interviews were audio recorded, transcribed verbatim, coded using an iteratively-developed codebook, and thematically analyzed. Interviews were conducted with 22 participants, consisting of 4 house officers, 6 junior obstetrics/gynecology residents, 8 senior obstetrics/gynecology residents, and 4 obstetrics/gynecology consultants. Doctors identified critical challenges faced at the patient, provider, and systems levels in detecting and managing preeclampsia, each of which mediates the health outcomes of a pregnancy complicated by preeclampsia. Challenges centered around three overarching global themes: (1) low education levels and health literacy among women, (2) insufficient number of healthcare providers highly trained in obstetric care, and (3) inadequate health infrastructure to support critically ill patients with preeclampsia. Recognizing and addressing root challenges to preeclampsia care has great potential to improve outcomes in pregnancies complicated by preeclampsia in low-resource settings.